Hak Asuh Anak Pasca Perceraian dalam Sistem Hukum Keluarga Islam (Studi Perbandingan di Indonesia dan Malaysia) - Muhammad Romi; Akbarizan; Akmal Abdul Munir (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2025)
Abstract This research discusses the regulation of child custody (hadhanah) after divorce in Islamic family law in Indonesia and Malaysia. The main focus lies on the juridical comparison and implementative practices in the two countries that have a background of Islamic law as part of their national legal systems. In Indonesia, child custody arrangements are regulated in the Compilation of Family Law, while in Malaysia it is regulated in the Islamic Family Law Act applicable in each state. This research uses a qualitative approach with a comparative law method and document analysis. The results of this study show that both countries recognize the principle of the best interests of the child as the main basis in determining custody, but there are differences in the decision-making mechanism, the role of Islamic courts, and the implementation of decisions in the field. This research recommends harmonizing the principles of child protection in the Islamic legal system with the development of international child rights to ensure optimal protection for children after divorce. Keywords: Child Custody, Divorce, Islamic Family Law